De novo‐generated small palindromes are characteristic of amplicon boundary junction of double minutes. Issue 4 (9th March 2013) - Zhu, Jing; Yu, Yang; Meng, Xiangning; Fan, Yihui; Zhang, Yu; Zhou, Chunshui; Yue, Zhichao; Jin, Yan; Zhang, Chunyu; Yu, Lisa; Ji, Wei; Jia, Xueyuan; et al.
<x xml:space="preserve">Abstract</x> Double minutes (DMs) are hallmarks of gene amplification. However, their molecular structure and the mechanisms of formation are largely unknown. To elucidate the structure and underlying molecular mechanism of DMs, we obtained and cloned DMs using microdissection; and degenerated oligonucleotide primed polymerase chain reaction (DOP‐PCR) from the ovarian cancer cell line UACC‐1598. Two large amplicons, the 284 kb AmpMYCN, originating from locus 2p24.3 and the 391 kb AmpEIF5A2, from locus 3q26.2, were found co‐amplified on the same DMs. The two amplicons are joined through a complex 7 kb junction DNA sequence. Analysis of the junction has revealed three de novo created small palindromes surrounding the six breakpoints. Consistent with these observations, we further found that 70% of the 57 reported DM junction sequences have de novo creation of small palindromic sequences surrounding the breakpoints. Together, our findings indicate that de novo‐generated small palindromic sequences are characteristic of amplicon boundary junctions on DMs. It is possible that the de novo‐generated small palindromic sequences, which may be generated through non‐homologous end joining in concert with a novel DNA repair machinery, play a common role in amplicon rejoining and gene amplification.